The extent of European power markets - Veit Böckers; Ulrich Heimeshoff (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
This paper analyzes the convergence process of Central-West European wholesale electricity markets from 2004 to the beginning of 2011. Jevon's law of price indifference is scrutinized using price correlation, parametric and nonparametric tests of price-differences and cointegration analysis. As a unique identifaction strategy national bank holidays are used as exogenous system shocks to trace the degree of market integration before the advent of the so-called market coupling of European power markets. In order to avoid overestimation of the degree of market integration, we specifically control for seasonal effects and common input factors. While the overall degree of integration between Germany and its neighbours has increased in the course of time, results suggest that only Austria and Germany already constitute a joint price area and that market coupling increases the convergence of markets at least between its participants.
Keywords: C32; L1; L40; L94; Q40; 330; Market Structure; Spatial Market Delineation; Time Series Econometrics; Energy Data; Electricity; Europe